Strut and tie model for the analysis of RC beam-column joints reinforced with non-metallic reinforcements - Jagadeesan, Saravanan; Kumaran, G. (Journal of Structural Engineering, 2024)
The present study is aimed to assess the joint shear strength by adopting strut and tie approach of the exterior concrete beam-column joints reinforced internally with non-metallic (GFRP-Glass Fibre Reinforced Polymer) reinforcements. Totally sixteen exterior RC beam-column joint specimens are cast with and without additional stirrups at the joint and tested under monotonically increasing loads on the beams and maintaining a constant service load on the column to satisfy the lateral equilibrium of the joint. The stiffness of the joint is found in terms of joint shear strength by adopting strut and tie approach. The results obtained from the analysis are compared with the experimental test results. It reveals that the joint shear strength is increased with the provision of additional stirrups at the joint. The strut and tie model proposed is overestimates the values of joint shear strength than the theoretical and experimental results.